The need for energy efficiency legislation in Malaysian building sector. A comparative study of south east Asian policies - Zaid, S.; Graham, P. (2012)
The Malaysian building sector approximately consumes 53% of national electricity generated, and emits 5,301 ktons of greenhouse gases (GHG) with an annual growth rate of 6.4%. While voluntary codes of practice for energy efficiency and use or renewable energy exist for non-residential buildings, Malaysia has yet to adopt mandatory energy efficiency legislation for its building sector. Mandatory building energy performance codes have been shown to be the most cost-efficient and effective policy instruments for reducing building energy-related greenhouse gas emissions. Therefore, without mandatory and comprehensive energy efficiency policy, Malaysia faces locking in substantial inefficiencies, and higher than necessary climate change impacts from its building sector. A comparison of energy efficiency policies from other South East Asian countries with similar climatic characteristics will be a valuable insight for Malaysia.